PENGEMBANGAN BLOG SEBAGAI SARANA DAN SUMBER BACAAN DALAM KEGIATAN LITERASI BAGI GURU DAN SISWA PADA MASA PANDEMI COVID-19 - Fransiska Arina Ehgo; I Made Sutama; I Wayan Artika (Dharmas Education Journal (DE_Journal), 2021)
This development research was motivated by the restriction of reading resources in the implementation of literacy activities for teachers and students during the Covid 19 pandemic. This research aimed at developing a blog as a tool and reading resources for literacy program during the Covid 19 pandemic and to elicit the teachers and students responses after using the blog. This study is employed (Research and Development). The study involved the bahasa Indonesia teacher and the class VIII 2 students SMP Negeri 6 Singaraja as the research subjects. The data were collected by a questionnaire and were analyzed descriptively and quantitatively. The results of the study showed that the blog was considered acceptable and feasible according to the results of content expert questionnaire by the average of 92,5. The score was in the interval 76 < SR ≤ 100 categorized as ‘Very Appropriate’. The results of media expert questionnaire was by the average of 77,5. The score was in the interval 76 < SR ≤ 100 considered to be ‘Very Appropriate’. Moreover, the results of the restricted try out by the teacher was by the average of 97,7. The scored was in the interval 76 < SR ≤ 100 considered to be ‘Very Appropriate’. In addition, the total score of the students’ responses was 75,5% in the interval 61 – 80 % categorized as ‘Appropriate”.